Potential role of folic acid in preventing male infertility associated with MTHFR gene C677T (rs1801133) polymorphism. Issue 1 (1st January 2021) - Alhumaydhi, Fahad A.; Mackawy, Amal M. H.; Morgan, Enas N.; Al Abdulmonem, Waleed; Alsagaby, Suliman A.; Alwashmi, Ameen S. S.; Aljohani, Abdullah S. M.; Aljasir, Mohammad A.; Almatroodi, Saleh A.; Alruwetei, Abdulmohsen M.; Mousa, Ayman M.
Abstract : Folic acid and methylenetetrahydrofolate reductase enzyme (MTHFR) gene C677T (rs1801133) SNP have been proofed to influence the spermatogenesis. This study aimed to investigate the biochemical, histological, and immunohistochemical (IHC) of adult male rabbits after induction of infertility by adenine, and the role of MTHFR C677T genotypes with or without folic acid therapy. Thirty adult male rabbits were divided into three groups: control (G1), adenine-induced infertility (G2), and adenine-induced infertility with folic acid therapy (G3). The PCR-RFLP was applied to detect the MTHFR C677T genotypes. Biochemical analyses of seminal fluid, homocysteine, and sex hormones were determined with histological and IHC examination of testicular tissue. Morphometric measurements and a TUNEL assay of seminiferous tubules were also performed. The results revealed a significant increase in homocysteine and sperm abnormalities, while sex hormones, sperm count and motility decreased significantly in the TT genotype compared with the CC genotype. Also, G2 displayed a significant increase in homocysteine and sperm abnormalities, with a significant decrease in sex hormones, sperm count and motility as compared to the G1 and G3. In conclusion, MTHFR 677C > T polymorphism is a genetic risk factor for male infertility and folic acid has a potential role in the treatment of male infertility.